2017
DOI: 10.1080/14786419.2017.1286481
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of honey supplemented with bee bread and propolis

Abstract: The aim of this work was characterisation of functional properties of honey enriched with propolis and beebread. In first step of experiment, soft propolis extract (SPEx) was obtained by extraction of propolis with ethanol. SPEx (0.25 to 1.0% w/w) as well as beebread (5 to 15% w/w) were implemented into natural honey. Fortified honeys were investigated in terms of total phenolic content, radical scavenging activity and ferric reducing antioxidant power, also their effects on the micro-organisms growth was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In addition, propolis which has an intensive, specific odor, and bitter taste, shows varies different properties such as antimicrobial, anti‐inflammatory, local anesthetic, antiparogen, antiviral, anticancerogenic (El‐khawaga, Salem, & Elshal, ), antioxidant, immune booster. Thus, propolis is used widely in different industries for different purposes (Kowalski & Makarewicz, ). In recent years, interest in natural additives has been increasing in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, propolis which has an intensive, specific odor, and bitter taste, shows varies different properties such as antimicrobial, anti‐inflammatory, local anesthetic, antiparogen, antiviral, anticancerogenic (El‐khawaga, Salem, & Elshal, ), antioxidant, immune booster. Thus, propolis is used widely in different industries for different purposes (Kowalski & Makarewicz, ). In recent years, interest in natural additives has been increasing in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors showed that mixtures of propolis and honey are advantageous against E . coli and MRSA as displaying larger halo inhibition zones than propolis or honey alone (Kowalski & Makarewicz, 2017; Osés et al, 2016). These authors suggest that using honey in combination with propolis strongly influence the bioactive properties of propolis, namely increasing its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, mixtures where propolis is the main component appear to preserve its antioxidant potential. Other authors studied the antioxidant potential of propolis and honey mixtures showing that the use of these two beehive products in combination improves the ability to scavenge free radicals of each beehive product alone and showing that the higher the percentage of propolis in the mixture, the higher the ability to reduce free radicals in a concentration‐dependent manner (Habryka et al, 2020; Kowalski & Makarewicz, 2017; Osés et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a combination of honey with bee bread (10-60%) resulted in a product with a significant total of phenolic, flavonoids content, and an antioxidant activity of 3.99, 0.3, and 4.08 more times, respectively, than the control sample [102]. Furthermore, a mixture of honey with propolis extract (1%) and bee bread (15%) resulted in a product with a high phenolic compounds content (150 mg/100 g) and a high antioxidant activity (6.5 more times) as evaluated by DPPH •+ [103].…”
Section: Enrichment Of Apiary Productsmentioning
confidence: 91%